2006
DOI: 10.1016/j.ijsolstr.2005.08.012
|View full text |Cite
|
Sign up to set email alerts
|

A micromechanical study of residual stress and its effect on transverse failure in polymer–matrix composites

Abstract: Cure residual stress and its effect on damage in unidirectional fibre-reinforced polymer-matrix composites under transverse loading were studied using a micromechanical unit cell model and the finite element method. The overall residual stress introduced from curing was determined by considering two contributions: volume shrinkage of matrix resin from the crosslink polymerization during isothermal curing and thermal contraction of both resin and fibre as a result of cooling from the curing temperature to room … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 35 publications
4
65
0
Order By: Relevance
“…High cure temperatures and fast heating/cooling rates can result in highly non-uniform temperature and cure gradients within the part resulting in differential curing and subsequent development of internal stresses. 3,[4][5][6]11 Similar effects in the form of a non-uniform distribution of in-plane shear stresses can arise due to constraints posed by tooling during processing. 10,12 A combination of the above-named residual stress mechanisms and manufacturing defects can cause local premature failure at lower load magnitudes than would otherwise be predicted in a defect-free composite structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High cure temperatures and fast heating/cooling rates can result in highly non-uniform temperature and cure gradients within the part resulting in differential curing and subsequent development of internal stresses. 3,[4][5][6]11 Similar effects in the form of a non-uniform distribution of in-plane shear stresses can arise due to constraints posed by tooling during processing. 10,12 A combination of the above-named residual stress mechanisms and manufacturing defects can cause local premature failure at lower load magnitudes than would otherwise be predicted in a defect-free composite structure.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, large process-induced residual stresses are known to induce matrix cracking, interfacial debonding and delamination in fibre-reinforced composites. 1 In other works, [4][5][6] demonstrated that for thick-walled composite tubes, residual stresses can be so great that matrix cracking was promoted. At a micromechanic level, Nedele and Wisnom 7 showed that process-induced stresses at the fibre-matrix interface can be as large as 30 MPa, due to the combination of hoop and radial stress components.…”
Section: Introductionmentioning
confidence: 99%
“…Rosso et al [21] estimated mesolevel cure-induced residual stresses by employing a plane-strain thermoelastic model of a unidirectional carbon fiber composite with hexagonal packing; however, they incorporated cure-shrinkage in an ad hoc manner by modifying the coefficient of thermal expansion of the resin only for a fixed temperature range (thereby not truly accounting for cure-dependent gelation effects). More recently, Zhao and coworkers have reported attempts to capture the cure phenomenology at the RVE level in greater detail with separate accounting for cureinduced shrinkage and thermal expansion effects in unidirectional composites by employing thermoelastic models [22] and thermoviscoelastic models [23]. These RVE simulations involved modeling of isothermal cure and cool-down stages of the thermal cycle.…”
Section: Background: Simulation Of Residual Stresses At Reinforcementmentioning
confidence: 99%
“…Chemical shrinkage was assumed to follow a linear dependence on conversion. Zhao et al [22,23] ignored the interdependence of cure and temperature, which might be a valid assumption for isothermal curing systems with low heats of reaction. However, such an assumption would not be valid for an RVE that is located in the core of a thick composite with a resin that has a very high heat of reaction.…”
Section: Background: Simulation Of Residual Stresses At Reinforcementmentioning
confidence: 99%
See 1 more Smart Citation